Women's artistic gymnastics routine composition at Rio 2016 Olympic Games: a technical analysis of balance beam and floor exercises routines - de Oliveira, M. H.; de Queiroz Lima, L. B.; Costa, A. R. (Science of Gymnastics Journal, 2022)
Artistic gymnastics is a sport comprising a variety of movements performed on apparatus, connected by the art of movement. The Code of Points is a document that brings together all the rules of this sport; it guides the work of coaches and gymnasts, helping to compose the routines presented in competitions. This study focuses on women's artistic gymnastics and the implementation of its rules, established by the Code of Points 2013-2016. It aims to analyze the elements that composed the gymnasts' routines during the last Olympic Games (Rio 2016) and identify the possible technical relations between the composition of the balance beam and the floor exercises in line with the current Code. For this purpose, we carried out a video analysis of 82 balance beam routines and 82 floor exercise routines, in total 164 routines performed by athletes competing in women's artistic gymnastics at the Rio 2016 Olympic Games qualifying competition. We observed that the Code of Points is still little explored, and gymnasts use only a few of the elements available. In this sense, the International Gymnastics Federation and, more specifically, the Code of Points, which regulates the sport, should devise strategies for better usage of the elements available within the stipulated rules.